HUBUNGAN BUDAYA ORGANISASI DENGAN LOYALITAS KARYAWAN PADA PT. SPANSET INDONESIA - Sinaga, Sautman; Tobing, Josephine (Fundamental Management Journal, 2016)
Human Resources is seen as an important asset a company has, since man is a dynamic resource and always needed in every process of production of goods and services. Human Resources is a strategic element in determining whether or not an organization healthy. Planned human resource development and sustainable is an absolute necessity, especially for the future of the organization. Human resource management is a means to improve the human quality, by improving human resources, improve well performance and organizational results, so as to realize what the objectives of the organization, so it is also necessary that the role of the leadership of the organization. Be aware that Human Resources is the basic capital in the process of development agencies or institutions, then the HR management needs to establish an organizational culture in which it is believed could form loyalty to the employee. The purpose of this study was to analyze the relationship between organizational culture and loyalty of employees at PT. SpanSet Indonesia. This study using SPSS version 22 to help the processing of data with a sample of 75 employees and the data were analyzed using Spearman Rank analysis.Keywords: organizational culture, employee loyalty